Home Biased Analysts in Emerging Markets - LAI, Sandy (Institutional Knowledge at Singapore Management University, 2008)
We find that local analyst recommendations are systematically more optimistic than foreign analyst recommendations in emerging markets. The effects of this novel home bias among local analysts overwhelm any information asymmetry between foreign and local analysts. Consequently, local analyst upgrades underperform foreign analyst upgrades, while local analyst downgrades outperform foreign analyst downgrades. Neither foreign investors, local institutions, nor retail investors appear to be fully cognizant of this bias. Trade reactions suggest that foreign investors overestimate the bias in foreign analyst recommendations while local institutions underestimate the bias in local analyst recommendations. These results are pervasive across countries, time periods, and stock groupings, and can be traced to investment banking pressure.